Pengaruh Kualitas Layanan dan Makanan Terhadap Kepuasan dan Loyalitas Pelanggan di Restoran Mie Gacoan - Farhan Mahruzzaman; Anak Agung Ketut Diatmika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the influence of service quality (Service Quality) and food quality (Food Quality) on customer satisfaction (Customer Satisfaction), as well as how customer satisfaction mediates the relationship between service quality and customer loyalty (Customer Loyalty) at Mie Gacoan, a restaurant in Tangerang Regency , Indonesia. Based on previous literature, these factors have been proven to be crucial in influencing customer experience and the long-term success of a business in the service industry. This research seeks to explore the complex dynamics between these variables by utilizing the SmartPLS method for data analysis. In this context, restaurant atmosphere is also considered as an important factor influencing customer satisfaction and loyalty. The main aim of this research is to provide in-depth insight into how Service Quality and Food Quality influence Customer Satisfaction, as well as how Customer Satisfaction strengthens Customer Loyalty. The practical implications of this research are expected to help Mie Gacoan and the restaurant industry in general in improving service strategies and product quality to strengthen long-term relationships with their customers.